2021
DOI: 10.1029/2020jd033534
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of Near‐Surface Daily Peak Wind Gusts Across Scandinavia: Observations and Model Simulations

Abstract: An observed daily peak wind gusts (DPWG) dataset over Scandinavia, consisting of time series from 127 meteorological stations across Finland, Norway and Sweden, has been created. This dataset provides high‐quality and homogenized near‐surface DPWG series for Scandinavia, spanning the longest available time period (1996–2016). The aim of this study is to evaluate the ability of two regional climate models (RCMs) in simulating DPWG winds. According to the observed DPWG climatology, meteorological stations are cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This study uses Climatol (Guijarro, 2017) to perform homogenization and missing data infilling on the raw 100 DAWS and DPWG series. A detailed description of the homogenization approach adopted in this study can be found in Azorin-Molina et al (2016), and Minola et al (2021).…”
Section: Wind Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study uses Climatol (Guijarro, 2017) to perform homogenization and missing data infilling on the raw 100 DAWS and DPWG series. A detailed description of the homogenization approach adopted in this study can be found in Azorin-Molina et al (2016), and Minola et al (2021).…”
Section: Wind Observationsmentioning
confidence: 99%
“…In 1996, SMHI started to install automatic weather stations across the country (Wern and Bärring, 2009), and it is only since then that hourly WS measurements were systematically recorded and hourly WG observations became available (Minola et al ., 2021). Thus, using hourly observations, daily wind series are prepared for the longest available time period of 1996–2019.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing availability of radar and wind tower data in recent years, many studies have focused on the statistical characteristics of surface gusts, such as climatic and seasonal variations in wind gusts (Azorin‐Molina et al., 2016; H. Guo et al., 2011; McVicar et al., 2012), numerical simulation of near‐surface gusts (Jung & Schindler, 2015, 2016; Minola et al., 2021), and the impact of complex terrain (Letson et al., 2019; Tieleman, 1992). However, many studies focus on near‐surface gust characteristics, and the characteristics of gusts hundreds of meters above the ground are still poorly understood (Belu & Koracin, 2013; Kahl et al., 2021; Suomi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%